2007
DOI: 10.2298/vsp0703183n
|View full text |Cite
|
Sign up to set email alerts
|

Forensic evaluation of persons with destructive behavior in the postwar Bosnia and Herzegovina

Abstract: High level of hetero-destruction in crime was proven in the study. Criminal acts and violations were committed by the persons without psychopathology, as well as by the persons with mental diseases, which rendered a forensic responsibility and analysis of such an influence on behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 16 publications
2
2
0
11
Order By: Relevance
“…Exploration phase of victimization in nonviolent victims is the highest after 8 weeks (65.00%), then after 4-8 weeks (57.50%) and in 7.50% of cases 4 weeks after rape. Results are similar to the ones in other studies [31][32] with higher anomia in our region, vulnerable family [14][15][16][17], sensational media [33] without monitor ing in B&H [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Exploration phase of victimization in nonviolent victims is the highest after 8 weeks (65.00%), then after 4-8 weeks (57.50%) and in 7.50% of cases 4 weeks after rape. Results are similar to the ones in other studies [31][32] with higher anomia in our region, vulnerable family [14][15][16][17], sensational media [33] without monitor ing in B&H [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 89%
“…They ask for help very late with already developed crisis of identity and sexuality and when severity of trauma creates disposition for psychotic crisis. High level of reproduction, depression, inability to control, destruction and psychotism confirm evolutional theory in the study [24], because Ego mechanisms do not control insticts [37]. Silver E. (2005) reported that "less than a half of victims were attacked two years before the interview, which shows us that personal experience of a violence can explain the proportion of non-violent victimization in the sample, and the connection between serious mental disorder and victimization is shown as individual tendency towards violence" [10].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Težina kliničke slike mentalnog poremećaja ima kliničke znake koji daju gubitak kontrole nad ponašanjem i doživljaj ugroženosti, impulsivnost, rezistentnost na tretman i bez pomoći socijalne sredine [3].…”
Section: Uvodunclassified